The Urgency of Hospital Internal Regulations in Governance of Indonesian National Army Hospital - Paulin Marwita; Sutarno; Adriano (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
This research analyzed the component of hospital bylaws in the corporate governance of the Indonesian National Army Hospital and the urgent of hospital bylaws in association with protection and legal certainty of the Indonesian National Army Hospital. As a legal subject, the Indonesian National Army Hospital has certain legal obligations and they are not free from lawsuits, therefore the Indonesian National Army Hospital must equip themselves with adaptive and up to date hospital by laws that provide protection and legal certainty to the medical officers in peace and armed-conflict time. The hospital bylaws must contain the characteristics of the Indonesian National Army Hospital including code of ethics for military medicine, Indonesian National Army law, military discipline law, military court law, humanitarian law, human rights law and also describing the relationship between the owner of the hospital, in this case the chief of the staff of the army, with the head of the hospital and medical staff. Therefore, this research is juridical-normative research using statute, conceptual and comparative approaches.